Propuesta de educación en valores a los niños/niñas de séptimo año de educación general básica de la Escuela “Dr. Plinio Fabara Zurita”, de la parroquia la Matriz del cantón Latacunga, provincia de Cotopaxi en el año 2011-2012 - Santander Rubio, Noemí Rebeca (2013)
The work presentd below, part of the location, recognition of the place and the people where you installed the educational institution in which there is an investigation and analysis of the situation of education in values with the actors involved in school, "Dr. Plinio Fabara Zurita" four corners chantan community and aims to identify the problems facing today and provide solutions to it. In this survey it was determinet that the community, as part of the problems among teachers.